Peningkatan Kemampuan Pemecahan Masalah Matematika Siswa Melalui Model Contekstual Teaching And Learning - Safri Tinamba; La Yusran La Kalamu (Jurnal Ilmiah Wahana Pendidikan, 2021)
The problems faced at SMP Negeri 5 Tidore Kepulauan related to learning mathematics activities in the classroom can be seen that some students do not understand math problems; unable to answer teacher questions, during the learning process; students are not able to respond well to the material being studied; the learning process of mathematics subjects for students is less fun; students find it difficult to master mathematics subject matter; most students are less motivated in participating in mathematics learning activities. In addition, based on the experience of researchers at the school, it is known that during learning activities there are still students who have not been able to express their opinions during learning, some students also seem less concerned about learning assignments. The formulation of this research is (1) Can the application of the contextual teaching and learning (CTL) learning model improve the mathematical problem-solving ability of the students of SMP Negeri 5 Tidore Islands City? (2) How do teachers and students manage learning based on the contextual teaching and learning (CTL) learning model? Thus, the objectives of this study were to determine: (1) the improvement of mathematical problem-solving abilities of students at SMP Negeri 5 Tidore Kepulauan City who were taught the contextual teaching and learning (CTL) model; (2) Analyzing the success of teachers and students in implementing learning based on the contextual teaching and learning (CTL) model. The type of research conducted is classroom action research (CAR). The sample in this study were students of class VIII SMP Negeri 5 Tidore Islands, as many as 24 students. Data retrieval in this study was carried out using observation sheets of teacher activities in managing learning and observations of student activities in learning, tests of mathematical problem-solving abilities. The results of the study show that CTL learning can improve students' mathematical problem-solving abilities